Implementasi Green Accounting Dalam Meningkatkan Keberlangsungan Operasional Pada Perusahaan Pakan Ternak PT Malindo Di Gresik - Marcella Trianita Abur; Rosaria Rudeng; Sinta Dewi; Maria Yovita R.Pandin (Jurnal Riset Akuntansi, 2023)
The purpose of this study is to determine how the company's green accounting implementation in improving operational activities. The type of research conducted in this study is quantitative research with the object of research, namely PT Malindo Feedmil in Gresik. The variables used are Return On Asset, Environmental Performance and Environmental Disclosure. Data analysis using SPSS 22, where the results of the analysis obtained are environmental performance (Environmental Performance) does not significantly affect ROA with a significance value of (0.927) ˃ 0.05), while Environmental Disclosure affects ROA with a significance value of 0.002 ˂ 0.05.